Sub-chronic and acute toxicity of aqueous extracts Salvia blancoana subsp. mesatlantica (Maire) Figuerola to rodents - Souad Maache; Adel Tahraoui; Najoua Soulo; Abdessamad Ait Benlabchir; Ghizlane Nouioura; Mohammed Bouslamti; Dara Aldisi; Hamza Saghrouchni; John P. Giesy; Mourad.A.M. Aboul-Soud; Badiaa Lyoussi; Ilham Elarabi (Toxicology Reports, 2024)
Background: Salvia blancoana subsp. mesatlantica (Maire) Figuerola (SBm) is a plant endemic to Morocco and is one of the less studied species of Salvia. Herbal therapy is becoming more and more popular, especially in underdeveloped nations where access to medicinal herbs is affordable. However, some plants demonstrated toxic effects in animals and humans. Objective: Our study aimed to evaluate the SBm-extract for both acute and sub-chronic toxicity. Methods: Aqueous extracts were obtained from the aerial parts of SBm collected from Immouzer Kander commune (Middle Atlas, Morocco). Total Phenolic Content (TPC) and Flavones and flavonols Content (FFC), Antioxidant activity (2,2-diphenyl-1-picrylhydrazyl (DPPH) and reducing power) was determined, and chemical composition was determined by High-Performance Liquid Chromatography with Diode Array Detection (HPLC-DAD). Toxicity tests were conducted on mice and rats. Results: In acute toxicity, Swiss albino mice (mass of 25–35 g) received SBm-extract orally and intraperitoneally at doses (0.5–11 g/kg, bm). The sub-chronic toxicity was tested in Wistar albino rats (mass of 200–240 g) for 90 days at doses of 0, 250, 500, or 1000 mg/kg, bm. Values of TPC and FFC were estimated to be 157.56 ± 0.32 mg GAE/g DW and 7.89 ± 0.05 mg QE/g DW, respectively. DPPH scavenging (IC50) was estimated to be 26.9 ± 0.08 µg/mL while reducing power was 12.41 ± 0.03 µg/mL. No toxicity or deaths were observed in acute tests after oral exposure, while intraperitoneal administration resulted in dose-dependent acute toxicity, with an LD50 value of 6.82 g/kg. In sub-chronic tests, most hematological and biochemical parameters remained unchanged, except for transient fluctuations in specific blood constituents and a transitory reduction in serum glucose levels observed at elevated dosages. Histopathological investigation revealed no organ abnormalities. The SBm-extract exhibited minimal toxicity, supporting its safe use. Conclusions: Despite the relevant results of this study, future studies need to confirm these findings and expand our understanding of the safety characteristics of Salvia. Further investigations are needed to explore the effects of other solvents on the extraction of bioactive compounds from the underground and aerial parts of this endemic species. Evaluation of other biological properties such as anti-microbial, anti-cancer, and anti-inflammatory activities are needed.